Performance of Ce-incorporated KIT-6 supported cobalt catalysts for fischer-Tropsch synthesis - Tan, Guodong; Li, Jinlin; Liew, Kong Yong (World Scientific Publishing Co Pte Ltd, 2011)
A series of Ce-incorporated structure of cubic large mesoporous molecular sieves, KIT-6, with different Ce contents were synthesized by a direct hydrothermal process. A sample of Ce-loaded KIT-6 material was synthesised by incipent wetness impregnation. Similarly, catalysts with 15 wt.% Co loading on the above supports were also synthesized by incipient wetness impregnation. The supports and catalysts were characterized by X-ray diffraction, diffuse reflectance UV-vis, solid-state 29Si magic-angle spinning nuclear magnetic resonance, H2-temperature programmed reduction, H2-temperature programmed desorption and oxygen titration. The structure of the KIT-6 support was well retained after Ce incorporation. Small amounts of Ce in the Co catalyst were found to improve the activity and increase the selectivity to C5+ hydrocarbons for Fischer–Tropsch synthesis, while larger amounts of Ce had the reverse effect. Meanwhile, methane selectivity shows an opposite trend as compared with that of C5+ selectivity. Ce-loaded KIT-6 supported Co catalyst showed lower activity than KIT-6 supported Co catalyst.